ASSOCIATION BETWEEN PR PROTEINS WITH RIBONUCLEASE ACTIVITY AND PLANT RESISTANCE AGAINST PATHOGENIC FUNGI - E. A. Filipenko; A. V. Kochetov; Y. Kanayama; V. I. Malinovsky; V. K. Shumny (Вавиловский журнал генетики и селекции)
Pathogenesis-related (PR) proteins participate in complex plant defense response to pathogens. It is known that members of two PR-proteins families (PR-4 and PR-10) exhibit ribonuclease activity in some cases. These proteins were found to be able to inhibit the growth of pathogenic fungi, and the ribonuclease activity is necessary for manifestation of this effect. This paper presents current data on molecular mechanisms governing the antifungal activity of PR-ribonucleases connected both with their direct cytotoxic impact on pathogen cells and with possible participation in induction of plant cell apoptosis and development of the hypersensitive reaction (HR).